The Pueblo of Sia, New Mexico - White, Leslie A., 1900-1975 (Bulletin (Smithsonian Institution. Bureau of American Ethnology), 1962)
"Sia was the only Keresan pueblo studied ethnologically in anything like systematic fashion during the 19th century. ... Most of the ethnographic fieldwork among the Keres has been done since World War I. ... My primary purpose in all my studies of the Keresan pueblos has been to learn as much as possible about their aboriginal culture. It is this that has been unique, and it is this that is disappearing from the face of the earth. ... I have, therefore, undertaken to present the culture of Sia in its actual and proper historical setting, i.e., as a culture in a process of change."--Introduction